Agronomic interventions for enhancing crop productivity under intensive crop cultivation - Kaur, Jagmohan; Kaur, Tarundeep; Kaur, Ramanjit (Indian Farming, 2021)
Different agronomic interventions under intensive crop cultivation which improve or maintain the field productivity as well as profitability on a long term basis are of immense importance. The practices like green manuring prior to sowing of kharif crops, inclusion of legumes in cereal based cropping systems, use of laser land leveller, and integration of organic manures with inorganic sources can help a lot in conserving natural resources. For successful crop production, stale bed technique can help to get rid of immense weed pressure.